Acceptability and feasibility of a mobile health application for blood pressure monitoring in rural Uganda. Issue 3 (8th January 2021) - Mugabirwe, Beatrice; Flickinger, Tabor; Cox, Lauren; Ariho, Pius; Dillingham, Rebecca; Okello, Samson
Abstract: Background: Mobile technologies to improve blood pressure control in resource-limited settings are needed. We adapted and evaluated the acceptability and feasibility of PositiveLinks, a mobile phone application for self-monitoring, social support, and engagement in care for people living with HIV, among patients with hypertension in rural Uganda. Methods: We enrolled adults on treatment for hypertension at Mbarara Regional Referral Hospital and Mbarara Municipal health center IV, southwestern Uganda. We provided and educated all participants on the use of PositiveLinks application and automated blood pressure monitors. We administered a baseline questionnaire and performed in-depth interviews 30 days later to explore acceptability, feasibility, medication adherence, social support, and blood pressure control. Results: A total of 37 participants completed the interviews, mean age of 58 years (SD 10.8) and 28 (75.7%) were female. All participants embraced the PositiveLinks mobile app and were enthusiastic about self-monitoring of blood pressure, 35 (94.6%) experienced peer to peer support. Among the 35 participants non-adherent to medications at baseline, 31 had improved medication adherence. All except 1 of the 31(83.8%) who had uncontrolled blood pressure at baseline, had self-reported controlled blood pressure after 30 days of use of PositiveLinks. Conclusion: Patients with hypertension in rural Uganda embraced the PositiveLinks mobile application and had improved medication adherence, social support, and blood pressure control. Further assessment of cost-effectiveness of the application in blood pressure control in resource-limited settings will be pursued in future studies.